Twilight - Godfrey, Wyck.; Mooradian, Greg.; Morgan, Mark.; Rosenfelt, Karen; Rosenberg, Melissa; Hardwicke, Catherine; Stewart, Kristen, 1990-; Pattinson, Robert; Burke, Billy; Greene, Ashley; Reed, Nikki, 1988-; Rathbone, Jackson; et al. (Santa Monica, Calif. : Summit Entertainment, 2009)
Isabella Swan moves to gloomy Forks, Washington to live with her father. She begins her junior year in high school and becomes fascinated by Edward Cullen who holds a dark secret known only by his family. To Edward, Bella is what he has waited 90 years for, a true soul mate. But he knows the further they progress in their relationship the more he is putting Bella and those close to her at risk. Edward tries to warn Bella that she should leave him, but she refuses. A new vampire finds it a challenge to hunt Bella down for her irresistible blood.
English and Spanish tracks: Dolby digital 5.1.
Title from container.
Based on the novel "Twilight" by Stephenie Meyer.
Originally released as a motion picture in 2008.
Special features: extended scenes; audio commentary by director Catherine Hardwicke, Kristen Stewart and Robert Pattinson; plus music videos; seven-part documentary; deleted scenes.
Director of photography, Elliot Davis ; editor, Nancy Richardson ; music, Carter Burwell.
Keywords: Cullen, Edward (Fictitious character) -- Drama; Swan, Bella (Fictitious character) -- Drama; Vampires -- Washington (State) -- Drama; Family secrets -- Washington (State) -- Drama; Eleventh grade (Education) -- Washington (State) -- Drama; Vampire films; Thrillers (Motion pictures); Feature films; Fantasy films; Suspense films; Films for the hearing impaired